Preparation method of moisture-locking and fragrance-retaining ceramic-coated special paper
The moisture-locking and fragrance-proof ceramic special paper prepared through the ceramic plating process uses water-based ceramics and polyurethane hybrid prepolymers to form a loose and porous structure, solving the problem of insufficient performance of aluminum-free moisture-proof fragrance-proof materials, and realizing the food It effectively blocks and fragrance protection effects in cigarette packaging, and meets the requirements of industrial production.
Patent Information
- Application Number
- CN202311260748.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-09-27
AI Technical Summary
In the food and tobacco packaging industry, it is difficult to develop aluminum-locked moisture-retaining materials with excellent performance and low cost. Especially in the context of promoting "dealuminization of packaging materials", existing barrier materials are moisturizing and There are shortcomings in fragrance preservation.
The ceramic plating process is used to prepare moisture-locking and fragrance-proof ceramic special paper. Through the combination of water-based ceramic and polyurethane hybrid prepolymer, a ceramic plating layer with loose porous structure is formed, which absorbs and stores water vapor and fragrance substances, and is dried. Quick release under conditions to achieve moisture-locking and fragrance-keeping effect.
This method achieves good barrier properties of water vapor and fragrance substances in food and tobacco packaging materials, and meets the needs of the "de-aluminization" era. At the same time, the process is simple, the raw and auxiliary materials are wide, and the price is low, which is suitable for industrial mass production.
Smart Images

Figure CN117144721B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic / polymer hybrid technology, relates to the preparation of ceramic-coated special paper, and in particular to a preparation method of moisture-locking and fragrance-retaining ceramic-coated special paper. Background Art
[0002] In recent years, as the tobacco industry has comprehensively promoted the "de-aluminization" of packaging materials, major raw and auxiliary material supply chains have responded one after another, forming a prairie fire, and gradually extended to the field of food and drug packaging. Aluminum-plated packaging materials have outstanding advantages, with excellent barrier properties and significant moisture-locking and fragrance-preserving effects on the wrapped objects. This is one of the important reasons why people have always favored aluminum packaging materials in the past. Whoever can make "de-aluminization of packaging materials" and bite off this "hard bone" will be able to seize the opportunity and occupy a considerable market share and profit. Many aluminum-free barrier materials have been reported one after another.
[0003] Performance and anti-aging application of nano-TiO2 / polyvinyl alcohol composite hydrogel membrane materials, New Chemical Materials, 2020, 48(6): 252-256; In order to explore the protective effect of nano-TiO2 / polyvinyl alcohol composite hydrogel membrane on textile materials, the PVA hydrogel membrane was modified with nano-TiO2, the nano-TiO2 content was changed, and the structure and performance of this series of membranes were investigated. The results show that when the addition amount of nano-TiO2 is 5.0%, its comprehensive performance is better. At this time, the tensile strength of the composite hydrogel film is 9.41MPa, the maximum ultraviolet transmittance is only 74.94%, and the transparency is 69.82%. A composite hydrogel film with a nano-TiO2 content of 5% was selected. Taking white cotton as an example, the synthesized composite hydrogel was used to treat the textile material samples. It was found that the weight loss rate of the treated samples did not change much after being irradiated with ultraviolet light for a period of time, while the fiber structure of the untreated samples was obviously damaged after being irradiated with ultraviolet light, with a weight loss rate of 6.77%, a peak force loss of 18.28%, and a significant decrease in whiteness value. This shows that the synthesized hydrogel has a protective effect on textile materials.
[0004] Preparation of sodium alginate gel and layered nanofilm by coordination of rare earth ions, Southeast University, Master's degree thesis, 2017; A sodium alginate hydrogel with sensitive response to pH, excellent mechanical properties, high water content and fluorescent properties was prepared. The preparation of sodium alginate hydrogel is mainly through the coordination and cross-linking of carboxylate ions and rare earth ions in sodium alginate to form a sodium alginate-rare earth ion hydrogel with a regular structure. It also shows high mechanical strength and excellent moisturizing properties, and has good application prospects in the field of food packaging.
[0005] The above reports are all focused on the preparation of barrier materials through hydrogel materials. In the actual industrialization, it is necessary to consider the manufacturing of finished products. Therefore, the development of an aluminum-free moisture-locking and fragrance-preserving material with excellent performance and low cost has become the focus of industry workers, and the ceramic plating process may be a good way to try it out. Summary of the invention
[0006] In order to comply with the "de-aluminization of packaging materials" advocated by the food and cigarette packaging industries and to have better moisture-retaining and aroma-locking functions, the purpose of the present invention is to disclose a method for preparing a moisture-locking and aroma-retaining ceramic-coated special paper, the main mechanism of which is that the mesoporous structure of the ceramic-coated layer provides adsorption and storage space for tiny water vapor molecules and volatile aroma substances, and the original adsorption energy of the ceramic-coated layer material is negligible, which provides favorable conditions for the rapid release of moisture and aroma substances to the surrounding environment under dry conditions.
[0007] To achieve the aforementioned objectives, the technical solution of the present invention is implemented through three major steps, namely (1) preparation of water-based ceramic, (2) preparation of water-based ceramic / polyurethane hybrid prepolymer, and (3) preparation of ceramic-coated specialty paper.
[0008] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0009] (1) Preparation of water-based ceramics: adjusting the temperature to 1-6°C, adding graphite powder, clay powder, nitrate and oxidant to concentrated acid at one time, stirring continuously for 1-3 hours, adding deionized water, adjusting the temperature to 40-60°C and maintaining for 0.5-4 hours; adding a neutralizing agent to adjust the pH value to 6.5-7.1, preferably 6.8, filtering under reduced pressure, washing the filter cake with a large amount of anhydrous ethanol and drying and storing, to obtain water-based ceramics;
[0010] The concentrated acid is concentrated sulfuric acid, fuming nitric acid, hydrofluoric acid, etc., preferably fuming nitric acid;
[0011] The graphite powder has a size of 40 to 80 meshes, preferably 60 meshes;
[0012] The clay powder is talc, bentonite, kaolin, diatomaceous earth, red clay, etc., preferably kaolin;
[0013] The nitrate is sodium nitrate, potassium nitrate, monomethylamine nitrate, etc., preferably sodium nitrate;
[0014] The oxidant is potassium permanganate, potassium chromate, potassium perchlorate, etc., preferably potassium perchlorate;
[0015] The neutralizing agent is ammonia water, sodium hydroxide, potassium hydroxide, etc., preferably sodium hydroxide;
[0016] The material ratio of the added graphite powder, clay, nitrate, oxidant and concentrated acid is 1.0-10.0g:20.0-60.0g:0.1-12.0g:9.0-50.0g:50-80ml, preferably 9.0g:45.4g:2.2g:31.8g:65ml; the volume ratio of the added deionized water to the concentrated acid is 15-60ml:50-80ml, preferably 50ml:65ml;
[0017] Preferably, after adjusting the temperature to 2°C, graphite powder, clay powder, nitrate and oxidant are added to the system at once, and after maintaining for 2.5 hours, deionized water is added to the system, and the temperature is adjusted and maintained at 46°C for 3 hours;
[0018] (2) Preparation of water-based ceramic / polyurethane hybrid prepolymer: polymer polyol, polyisocyanate and organic solvent are mixed, and the temperature is adjusted to 40-70°C, and then the chain extender and catalyst are added at one time. After 2-6 hours, the temperature is adjusted to 55-90°C, and a neutralizer is added through a constant pressure dropping funnel for 15-30 minutes until the pH is 7.0-7.5; after adjusting the temperature to 60-80°C, the above-mentioned water-based ceramic is added, and the organic solvent is removed by reduced pressure distillation after reacting for 1-3 hours to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0019] The polymeric polyol is polycarbonate diol, polyfuran diol, polyethylene glycol, low-branching polyester polyol, polyether polyol, polycaprolactone (diol), polytetramethylene glycol, etc., preferably polytetramethylene glycol;
[0020] The polyisocyanate is toluene diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,12-dodecane diisocyanate, dimethylbiphenyl diisocyanate, 1,5-naphthalene diisocyanate, etc., preferably dimethylbiphenyl diisocyanate;
[0021] The organic solvent is acetone, butanone, methyl ethyl ketone, dioxane, N,N-dimethylamide, N-methylpyrrolidone, etc., preferably N-methylpyrrolidone;
[0022] The chain extender is 2,2-dimethylol propionic acid, 2,2-dimethylol butyric acid, naphthalene phenol, 3,5-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, etc., preferably 2,2-dimethylol butyric acid;
[0023] The catalyst is potassium isooctanoate, dioctyltin dithiol, dibutyltin oxide, dibutyltin diacetate, phenylmercuric propionate, etc., preferably dibutyltin diacetate;
[0024] The neutralizing agent is triethylamine, ammonia water, sodium hydroxide, etc., preferably triethylamine;
[0025] The amount of the polymer polyol added is 0.98-1.01 mmol, preferably 0.99 mmol; the material ratio of the added polyisocyanate, organic solvent and polymer polyol is 1.02-1.15 mmol:10-20 ml:0.98-1.01 mmol, preferably 1.05 mmol:12 ml:0.99 mmol;
[0026] The material ratio of the chain extender added to the polymer polyol is 0.45-0.63 mmol:0.98-1.01 mmol, preferably 0.47 mmol:0.99 mmol;
[0027] The material ratio of the catalyst addition amount to the polymerized polyol is 0.03-0.55 mg:0.98-1.01 mmol, preferably 0.51 mg:0.99 mmol;
[0028] The volume ratio of the deionized water added to the organic solvent is 80-150 ml:10-20 ml, preferably 120 ml:12 ml;
[0029] The material ratio of the water-based ceramic addition amount to the polymerized polyol is 55.0-92.7 g:0.98-1.01 mmol, preferably 87.4 g:0.99 mmol;
[0030] Further preferably, when the above preferred embodiment is selected, a neutralizing agent is added until the pH is stabilized at 7.2;
[0031] Further preferably, when the above preferred scheme is selected, the chain extender and catalyst are added at one time after the system temperature is adjusted to 45°C, and 5 ml of organic solvent is used to rinse the tube wall; after 3 hours, the temperature is adjusted to 62°C, and a neutralizer is added to the system through a constant pressure dropping funnel within 20 minutes, and the reaction is maintained for 42 minutes; deionized water is added through a constant pressure dropping funnel within 9 minutes, and the water-based ceramic is added after the temperature is adjusted to 76°C, and the organic solvent is removed by reduced pressure distillation after the reaction is maintained for 2 hours;
[0032] (3) Preparation of ceramic-coated special paper: the water-based ceramic / polyurethane hybrid prepolymer obtained above is measured, a foaming agent and a stabilizer are added, and then the prepolymer is dispersed uniformly in an ultrasonic water bath, and the obtained dispersion is uniformly coated on the surface of the paper by a web coating method, and the surface drying and curing parameters are controlled to perform coating and curing, and the operation is repeated multiple times until the dry coating amount reaches 4.5 to 12.5 g / m 2 , that is, ceramic-coated special paper is obtained;
[0033] The foaming agent is ammonium bicarbonate, azodicarbonamide, monofluorodichloroethane, monochlorotrifluoropropylene, 4,4-oxybisbenzenesulfonylhydrazide, N,N′-dinitrosopentamethylenetetramine, etc., preferably azodicarbonamide;
[0034] The stabilizer is citric acid, sodium alginate, sodium dodecylbenzene sulfonate, etc., preferably sodium dodecylbenzene sulfonate;
[0035] The water-based ceramic / polyurethane hybrid prepolymer is measured to be 40-60 ml, preferably 45 ml;
[0036] The material ratio of the foaming agent and stabilizer to the water-based ceramic / polyurethane hybrid prepolymer is 0.5-10g:0.2-0.8mg:40-60ml, preferably 8g:0.3mg:45ml;
[0037] The surface drying and curing parameters during coating are: temperature 50-60°C-80-100°C-110-120°C-110-140°C-105-160°C-60-90°C, winder and unwinder speed 40-90m / min, unwinding tension 25-50N / m, winding tension 32-55N / m; preferably, temperature 52°C-83°C-115°C-120°C-135°C-70°C, winder and unwinder speed 70m / min, unwinding tension 31N / m, winding tension 47N / m;
[0038] Preferably, the coating and curing operations are repeated several times until the dry coating amount reaches 8.6 g / m 2 .
[0039] Experimental methods
[0040] (1) Coating, surface drying and curing
[0041] The coating, surface drying and curing were completed by a gravure coating and combination printing press (JD-XL330 prototype, Jiangxi Zhongjing Group). The printing press was loaded with 42g / m 2 ×220mm×5300m double-sided glossy virgin white paper, transfer the ultrasonic dispersion mixed liquid provided in (3) to the material tank, set the machine parameters and complete the winding of the composite paper.
[0042] (2) Field emission scanning electron microscopy (SEM) characterization
[0043] The coated surface of the ceramic-coated special paper prepared in Example 1, the 42 g / m 2 ×220mm×5300m double-sided glossy white paper surface microstructure characterization. Cut the sample to be characterized into appropriate specifications and fix it under the observation microscope to record the microstructure and morphology of the two paper surfaces at a size of 2.00μm.
[0044] (3) Specific surface area test
[0045] A fully automatic specific surface area and pore size analyzer (3H-2000PSI, Beijing Best Instrument Technology Co., Ltd.) was used to measure the specific surface areas of the coated surface of the ceramic-coated specialty paper and the double-sided glossy original white paper prepared in Example 1 using the N2 static adsorption method and the BET multi-point algorithm.
[0046] (4) Moisture-proof and moisture-retaining performance test
[0047] The moisture permeability of the coated surface of the ceramic-coated specialty paper and the double-sided glossy original white paper prepared in Example 1 was tested using a moisture permeability tester (Permatran-W3 / 33, MOCON, USA) in accordance with GB / T 26253-2010 "Determination of water vapor transmission rate of plastic films and sheets - Infrared detector method" as the standard.
[0048] (5) Oxygen permeability test
[0049] The oxygen permeability of the coated surface of the ceramic-coated special paper and the double-sided glossy original white paper prepared in Example 1 was tested using an oxygen permeability tester (OX-TRAN 2 / 21, MOCON, USA) in accordance with GB / T 19789-2005 "Oxidation permeability test of plastic films and sheets for packaging materials - Coulometric detection method" as the standard.
[0050] Beneficial Effects
[0051] The present invention obtains active water-based ceramic by oxidation reaction, and the surface of the water-based ceramic contains rich hydroxyl groups, carboxyl groups, etc. Then the water-based ceramic is hybridized with polyurethane chain segments on the surface of ordinary double-sided smooth original paper to form a functional structural coating that is both loose and porous and dense. It should be emphasized that when this type of ceramic-coated special paper is made into packaging materials, the coating surface is placed on the inside. The ceramic-plated special paper provided by the present invention has a loose porous structure of a ceramic-plated layer, which is conducive to combining with water molecules under relatively humid conditions and releasing water molecules when drying. This is mainly due to the fact that the combination of water-based ceramic and polyurethane resin has a good regulating effect on the overall specific surface area of the coating, and can absorb more water vapor molecules. In addition, the water-based ceramic hybrid polyurethane itself does not form a strong chemical bond with water molecules, so it can play a role in fine-tuning and rebalancing the humidity of the environment inside the package; at the same time, since the ceramic-plated layer itself is dried and cured on the surface of the paper through a coating process, it can greatly fill the original inherent pores of the paper. It is found through moisture permeability and oxygen permeability tests that it has a good barrier effect on water vapor and volatile aroma substances, which conforms to the trend of the times of "de-aluminization" of moisture-locking and aroma-preserving materials; and the preparation process of the ceramic-plated special paper is simple, the raw and auxiliary materials are widely available, the price is low, and the safety is reliable, meeting the basic requirements of industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1.SEM images of paper surfaces, where (a) is the coated surface of the ceramic-coated specialty paper obtained in Example 1, and (b) is the surface of the original double-sided glossy white paper. DETAILED DESCRIPTION
[0053] The present invention is described in detail below in conjunction with specific embodiments, and the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
[0054] Example 1
[0055] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0056] Add 65ml of fuming nitric acid to a 250ml three-necked flask, immerse the three-necked flask in a water bath and equip it with a mechanical stirrer and a thermometer, and maintain the stirring rate at 300r / min until the reaction is completed. After adjusting the temperature to 2°C, add 9.0g of 60-mesh graphite powder, 45.4g of kaolin, 2.2g of sodium nitrate and 31.8g of potassium perchlorate to the system at one time, maintain for 2.5h, add 50ml of deionized water to the system, adjust and maintain the temperature at 46°C for 3h; add sodium hydroxide to the system and adjust the pH value to 6.8, then filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it for storage; water-based ceramics are obtained;
[0057] 0.99 mmol polytetramethylene glycol, 1.05 mmol dimethylbiphenyl diisocyanate and 12 ml N-methylpyrrolidone were added to a 500 ml four-necked flask. The four-necked flask was immersed in an oil bath and equipped with a mechanical stirrer, a thermometer, a condenser and a constant pressure dropping funnel. The stirring rate was maintained at 500 r / min until the reaction was completed. After adjusting the system temperature to 45°C, 0.47mmol 2,2-dihydroxymethylbutyric acid and 0.51mg dibutyltin diacetate were added at once, and 5ml of organic solvent was used to rinse the tube wall; after 3 hours, the temperature was adjusted to 62°C, and triethylamine was added to the system through a constant pressure dropping funnel within 20 minutes to stabilize at 7.2, and the reaction was maintained for 42 minutes; 120ml of deionized water was added through a constant pressure dropping funnel within 5-15min9min, and 87.4g of the above-obtained water-based ceramic was added after adjusting the temperature to 76°C. After maintaining the reaction for 2 hours, the organic solvent was removed by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0058] 45 ml of the above-obtained water-based ceramic / polyurethane hybrid prepolymer was measured and transferred to a 100 ml round-bottom flask, 8 g of azodicarbonamide and 0.3 mg of sodium dodecylbenzene sulfonate were added and dispersed evenly in an ultrasonic water bath at room temperature, and the obtained dispersion was evenly coated on the surface of the paper by web coating. The surface drying and curing parameters during coating were controlled. The temperature of the 6-section oven was controlled at 52°C-83°C-115°C-120°C-135°C-70°C, the speed of the unwinding machine was controlled at 70 m / min, the unwinding tension was controlled at 31 N / m, and the winding tension was controlled at 47 N / m. The coating and paper were combined, and the coating and curing operations were repeated many times until the dry coating amount reached 8.6 g / m 2 , that is, ceramic-coated special paper is obtained.
[0059] Example 2
[0060] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0061] Add 50ml of fuming nitric acid to a 250ml three-necked flask, immerse the three-necked flask in a water bath and equip it with a mechanical stirrer and a thermometer, and maintain the stirring rate at 300r / min until the reaction is completed. After adjusting the temperature to 1°C, add 1.0g of 40-mesh graphite powder, 20.0g of kaolin, 0.1g of sodium nitrate, and 9.0g of potassium perchlorate to the system at one time, maintain for 1h, add 15ml of deionized water to the system, adjust and maintain the temperature at 40°C for 0.5h; add sodium hydroxide to the system and adjust the pH value to 6.5, then filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it for storage; water-based ceramics are obtained;
[0062] 0.98 mmol polytetramethylene glycol, 1.02 mmol dimethylbiphenyl diisocyanate and 10 ml N-methylpyrrolidone were added to a 500 ml four-necked flask. The four-necked flask was immersed in an oil bath and equipped with a mechanical stirrer, a thermometer, a condenser and a constant pressure dropping funnel. The stirring rate was maintained at 500 r / min until the reaction was completed. After adjusting the system temperature to 40°C, 0.45mmol 2,2-dihydroxymethylbutyric acid and 0.03mg dibutyltin diacetate were added at once, and 5ml of organic solvent was used to rinse the tube wall; after 2 hours, the temperature was adjusted to 55°C, and triethylamine was added to the system through a constant pressure dropping funnel within 15 minutes until the pH value was stabilized at 7.0, and the reaction was maintained for 20 minutes; 80ml of deionized water was added through a constant pressure dropping funnel within 5 minutes, and 55.0g of the above-obtained water-based ceramic was added after adjusting the temperature to 60°C. After maintaining the reaction for 1 hour, the organic solvent was removed by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0063] 40 ml of the above-obtained water-based ceramic / polyurethane hybrid prepolymer was measured and transferred to a 100 ml round-bottom flask, 0.5 g of azodicarbonamide and 0.2 mg of sodium dodecylbenzene sulfonate were added and dispersed evenly in an ultrasonic water bath at room temperature, and the obtained dispersion was evenly coated on the surface of the paper by roll paper coating, and the surface drying and curing parameters were controlled during coating. The temperature of the 6-section oven was controlled at 50°C-80°C-110°C-110°C-105°C-60°C, the speed of the unwinding machine was controlled at 40 m / min, the unwinding tension was controlled at 25 N / m, and the winding tension was controlled at 32 N / m. The coating and paper were combined, and the coating and curing operations were repeated many times until the dry coating amount reached 4.5 g / m 2 , that is, ceramic-coated special paper is obtained.
[0064] Example 3
[0065] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0066] Add 80ml of fuming nitric acid to a 250ml three-necked flask, immerse the three-necked flask in a water bath and equip it with a mechanical stirrer and a thermometer, and maintain the stirring rate at 300r / min until the reaction is completed. After adjusting the temperature to 6°C, add 10.0g of 80-mesh graphite powder, 60.0g of kaolin, 12.0g of sodium nitrate and 50.0g of potassium perchlorate to the system at one time, maintain for 3h, add 60ml of deionized water to the system, adjust and maintain the temperature at 60°C for 4h; add sodium hydroxide to the system and adjust the pH value to 7.1, then filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it for storage; water-based ceramics are obtained;
[0067] Add 1.01mmol polytetramethylene glycol, 1.15mmol dimethylbiphenyl diisocyanate and 20ml N-methylpyrrolidone into a 500ml four-necked flask. The four-necked flask is immersed in an oil bath and equipped with a mechanical stirrer, a thermometer, a condenser and a constant pressure dropping funnel. Maintain a stirring rate of 500r / min until the reaction is completed. After adjusting the system temperature to 70°C, 0.63mmol 2,2-dihydroxymethylbutyric acid and 0.55mg dibutyltin diacetate were added at once, and 5ml of organic solvent was used to rinse the tube wall; after 6 hours, the temperature was adjusted to 90°C, and triethylamine was added to the system through a constant pressure dropping funnel within 30 minutes until the pH value was stabilized at 7.5, and the reaction was maintained for 60 minutes; 150ml of deionized water was added through a constant pressure dropping funnel within 15 minutes, and 92.7g of the above-obtained water-based ceramic was added after adjusting the temperature to 80°C. After maintaining the reaction for 3 hours, the organic solvent was removed by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0068] 60 ml of the above-obtained water-based ceramic / polyurethane hybrid prepolymer was measured and transferred to a 100 ml round-bottom flask, 10 g of azodicarbonamide and 0.8 mg of sodium dodecylbenzene sulfonate were added and dispersed evenly in an ultrasonic water bath at room temperature, and the obtained dispersion was evenly coated on the surface of the paper by web coating, and the surface drying and curing parameters during coating were controlled. The temperature of the 6-section oven was controlled at 60°C-100°C-120°C-140°C-160°C-90°C, the speed of the unwinding machine was controlled at 90 m / min, the unwinding tension was controlled at 50 N / m, and the winding tension was controlled at 55 N / m. The coating and paper were combined, and the coating and curing operations were repeated many times until the dry coating amount reached 12.5 g / m 2 , that is, ceramic-coated special paper is obtained.
[0069] Example 4
[0070] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0071] Add 52ml concentrated sulfuric acid to a 250ml three-necked flask, immerse the flask in a water bath and equip it with a mechanical stirrer and a thermometer, and maintain the stirring rate at 300r / min until the reaction is complete. After adjusting the temperature to 3°C, add 7.2g of 50-mesh graphite powder, 32.8g of talc, 8.5g of potassium nitrate and 11.6g of potassium permanganate to the system at one time, maintain for 2h, add 40ml of deionized water to the system, adjust and maintain the temperature at 51°C for 1h; add ammonia water to the system and adjust the pH value to 6.6, then filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it for storage; water-based ceramics are obtained;
[0072] Add 1.00mmol polycarbonate diol, 1.01mmol toluene diisocyanate and 15ml acetone to a 500ml four-necked flask. The four-necked flask is immersed in an oil bath and equipped with mechanical stirring, a thermometer, a condenser and a constant pressure dropping funnel. Maintain the stirring rate at 500r / min until the reaction is completed. Adjust the system temperature to 46°C, add 0.58mmol 2,2-dihydroxymethylpropionic acid and 0.12mg potassium isooctanoate at one time, and rinse the tube wall with 5ml organic solvent; after 4h, adjust the temperature to 88°C, add ammonia water to the system through a constant pressure dropping funnel within 18min until the pH stabilizes at 7.1, and maintain the reaction for 58min; add 140ml deionized water through a constant pressure dropping funnel within 10min, adjust the temperature to 75°C, add 63.1g of the above-obtained water-based ceramic, maintain the reaction for 2.5h, and then remove the organic solvent by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0073] 50 ml of the above-obtained water-based ceramic / polyurethane hybrid prepolymer was measured and transferred to a 100 ml round-bottom flask, 1.2 g of ammonium bicarbonate and 0.4 mg of sodium alginate and sodium dodecylbenzene sulfonate were added, and then dispersed evenly in an ultrasonic water bath at room temperature. The obtained dispersion was evenly coated on the surface of the paper by web coating. The surface drying and curing parameters during coating were controlled. The temperature of the 6-section oven was controlled at 55°C-85°C-112°C-115°C-120°C-80°C, the speed of the unwinding machine was controlled at 50 m / min, the unwinding tension was controlled at 30 N / m, and the winding tension was controlled at 48 N / m. The coating and paper were combined, and the coating and curing operations were repeated many times until the dry coating amount reached 5.5 g / m 2 , that is, ceramic-coated special paper is obtained.
[0074] Example 5
[0075] A method for preparing moisture-locking and fragrance-retaining ceramic-coated special paper comprises the following steps:
[0076] Add 77ml of hydrofluoric acid to a 250ml three-necked flask, immerse the three-necked flask in a water bath and equip it with a mechanical stirrer and a thermometer, and maintain the stirring rate at 300r / min until the reaction is complete. After adjusting the temperature to 5°C, add 2.9g of 70-mesh graphite powder, 48.4g of red clay, 8.9g of monomethylamine nitrate and 11.4g of potassium chromate to the system at one time, maintain for 1.5h, add 46ml of deionized water to the system, adjust and maintain the temperature at 55°C for 2h; add potassium hydroxide to the system and adjust the pH value to 7.0, then filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it for storage; water-based ceramics are obtained;
[0077] Add 1.01mmol polycaprolactone (diol), 1.14mmol 1,5-naphthalene diisocyanate and 16ml N,N-dimethylamide into a 500ml four-necked flask. The four-necked flask is immersed in an oil bath and equipped with a mechanical stirrer, a thermometer, a condenser and a constant pressure dropping funnel. Maintain a stirring rate of 500r / min until the reaction is completed. After adjusting the system temperature to 54°C, 0.52mmol 3,4,5-trihydroxybenzoic acid and 0.08mg phenylmercuric propionate were added at once, and 5ml of organic solvent was used to rinse the tube wall; after 5 hours, the temperature was adjusted to 72°C, and sodium hydroxide was added to the system through a constant pressure dropping funnel within 32 minutes until the pH value was stabilized at 7.4, and the reaction was maintained for 56 minutes; 130ml of deionized water was added through a constant pressure dropping funnel within 12 minutes, and 59.7g of the above-obtained water-based ceramic was added after adjusting the temperature to 75°C. After maintaining the reaction for 2.5 hours, the organic solvent was removed by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer;
[0078] 59 ml of the water-based ceramic / polyurethane hybrid prepolymer obtained above was measured and transferred to a 100 ml round-bottom flask, 6.7 g of N,N′-dinitrosopentamethylenetetramine and 0.7 mg of citric acid were added and dispersed evenly in an ultrasonic water bath at room temperature, and the obtained dispersion was evenly coated on the surface of the paper by web coating. The surface drying and curing parameters during coating were controlled. The temperature of the 6-section oven was controlled at 57°C-92°C-116°C-119°C-155°C-88°C, the speed of the unwinding machine was controlled at 60 m / min, the unwinding tension was controlled at 42 N / m, and the winding tension was controlled at 53 N / m. The coating and paper were combined, and the coating and curing operations were repeated many times until the dry coating amount reached 9.2 g / m 2 , that is, ceramic-coated special paper is obtained.
[0079] The coated surface of the ceramic-coated special paper and the double-sided glossy original white paper obtained in Example 1 were characterized by SEM. The results are as follows: Figure 1 As shown. It can be clearly seen that the coated surface of ceramic-coated specialty paper has many loose pore structures. Compared with the smooth surface of double-sided glossy original white paper, it is more conducive to the non-chemical binding force of water vapor molecules hiding in the gaps under the siphon effect under wet conditions. When the humidity in the environment is low, these locked moisture will be gradually released, forming a micro-adjustment of the system environment humidity.
[0080] In order to further illustrate the physical parameters of the coated surface of ceramic-coated special paper and the surface of double-sided glossy original white paper, the above two types of paper were characterized by specific surface area, and the results are shown in Table 1. It can be fully seen from the table that the ceramic-coated coating has a larger specific surface area than the double-sided glossy original white paper surface, which is consistent with the microstructure observed by SEM.
[0081] Table 1. Test results of paper surface specific area
[0082]
[0083] The water vapor and oxygen permeability of the above two papers were characterized by oxygen permeability and moisture permeability tester, and the moisture-proof and aroma-preserving properties of the two papers were quantitatively analyzed, and the results are shown in Table 2. It can be clearly seen that the water vapor permeability of ceramic-coated special paper is significantly lower than that of double-sided glossy original white paper, and the packaging material made of it has better moisture barrier performance; on the other hand, the oxygen permeability of ceramic-coated special paper is also significantly lower than that of double-sided glossy original white paper, which is mainly attributed to the formation of a denser film material on the surface of the ceramic-coated coating, which has a stronger barrier performance for small molecular gases, and therefore should also have a good barrier force for volatile aroma substances.
[0084] Table 2. Paper moisture and oxygen permeability test results
[0085]
[0086] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper, characterized in that: The steps include: (1) Preparation of water-based ceramics: adjust the temperature to 1-6°C, add graphite powder, clay powder, nitrate and oxidant to concentrated acid at one time, stir continuously for 1-3 hours, add deionized water, adjust the temperature to 40-60°C and maintain for 0.5-4 hours; add neutralizer to adjust the pH value to 6.5-7.1, filter under reduced pressure, rinse the filter cake with a large amount of anhydrous ethanol and dry it to obtain water-based ceramics; add graphite powder, clay, nitrate, oxidant and The material ratio of concentrated acid is 1.0~10.0g:20.0~60.0g:0.1~12.0g:9.0~50.0g:50~80ml; the volume ratio of added deionized water to concentrated acid is 15~60ml:50~80ml; wherein the concentrated acid is concentrated sulfuric acid, fuming nitric acid or hydrofluoric acid; the graphite powder size is 40~80 mesh; the clay powder is talc, bentonite, kaolin, diatomaceous earth or red clay; (2) Preparation of water-based ceramic / polyurethane hybrid prepolymer: Mix the polymer polyol, polyisocyanate and organic solvent, adjust the system temperature to 40-70°C, then add the chain extender and catalyst at one time, adjust the temperature to 55-90°C after 2-6 hours, add the neutralizer through a constant pressure dropping funnel over 15-30 minutes until the pH is 7.0-7.5; adjust the temperature to 60-80°C, add the above water-based ceramic, maintain the reaction for 1-3 hours, and then remove the organic solvent by reduced pressure distillation to obtain a milky yellow water-based ceramic / polyurethane hybrid prepolymer; the amount of polymer polyol added is 0.98-1.01 m mol; the material ratio of the added polyisocyanate, organic solvent and polymer polyol is 1.02~1.15mmol:10~20ml:0.98~1.01mmol; the material ratio of the added amount of chain extender and polymer polyol is 0.45~0.63mmol:0.98~1.01mmol; the material ratio of the added amount of catalyst and polymer polyol is 0.03~0.55mg:0.98~1.01mmol; the material ratio of the added amount of water-based ceramic and polymer polyol is 55.0~92.7g:0.98~1.01mmol; (3) Preparation of ceramic-coated special paper: the water-based ceramic / polyurethane hybrid prepolymer obtained above is measured, a foaming agent and a stabilizer are added, and then the dispersion is evenly dispersed in an ultrasonic water bath, and the obtained dispersion is evenly coated on the surface of the paper by a web coating method, and the surface drying and curing parameters are controlled to perform coating and curing, and the operation is repeated multiple times until the dry coating amount reaches 4.5-12.5 g / m 2 , that is, to obtain; measure 40-60 ml of water-based ceramic / polyurethane hybrid prepolymer; the material ratio of the added amount of foaming agent and stabilizer to the water-based ceramic / polyurethane hybrid prepolymer is 0.5-10 g:0.2-0.8 mg:40-60 ml; wherein the foaming agent is ammonium bicarbonate, azodicarbonamide, monofluorodichloroethane, monochlorotrifluoropropylene, 4,4-oxybisbenzenesulfonylhydrazine or N,N′-dinitrosopentamethylenetetramine.
2. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), a neutralizing agent is added to adjust the pH value to 6.8, the mixture is filtered under reduced pressure, and the filter cake is rinsed with a large amount of anhydrous ethanol and dried to obtain a water-based ceramic.
3. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the material ratio of the added graphite powder, clay, nitrate, oxidant and concentrated acid is 9.0g:45.4g:2.2g:31.8g:65ml.
4. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the volume ratio of deionized water to concentrated acid is 50ml:65ml.
5. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the concentrated acid is fuming nitric acid.
6. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the graphite powder has a size of 60 mesh.
7. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the clay powder is kaolin.
8. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the nitrate is sodium nitrate, potassium nitrate or monomethylammonium nitrate; the oxidant is potassium permanganate, potassium chromate or potassium perchlorate; and the neutralizer is ammonia water, sodium hydroxide or potassium hydroxide.
9. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the nitrate is sodium nitrate.
10. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the oxidant is potassium perchlorate.
11. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (1), the neutralizing agent is sodium hydroxide.
12. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the amount of polymer polyol added is 0.99 mmol.
13. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the material ratio of the added polyisocyanate, organic solvent and polymer polyol is 1.05mmol:12ml:0.99mmol.
14. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the material ratio of the chain extender added to the polymer polyol is 0.47mmol:0.99mmol.
15. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the material ratio of the catalyst added to the polymer polyol is 0.51 mg:0.99 mmol.
16. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the material ratio of the water-based ceramic added to the polymer polyol is 87.4 g:0.99 mmol.
17. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), a neutralizing agent is added until the pH stabilizes at 7.
2.
18. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the system temperature is adjusted to 45°C and then the chain extender and catalyst are added at once. After 3 hours, the temperature is adjusted to 62°C, and the neutralizer is added to the system through a constant pressure dropping funnel within 20 minutes, and the reaction is maintained for 42 minutes. Deionized water is added through a constant pressure dropping funnel within 9 minutes, and the temperature is adjusted to 76°C and then the water-based ceramic is added. After the reaction is maintained for 2 hours, the organic solvent is removed by reduced pressure distillation.
19. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the polymer polyol is polycarbonate diol, polyfuran diol, polyethylene glycol, low-branching polyester polyol, polyether polyol, polycaprolactone diol or polytetramethylene glycol; the polyisocyanate is toluene diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,12-dodecane diisocyanate, dimethyl diphenyl diisocyanate or 1,5-naphthalene diisocyanate; the organic solvent is Acetone, butanone, methyl ethyl ketone, dioxane, N,N-dimethylamide or N-methylpyrrolidone; the chain extender is 2,2-dihydroxymethylpropionic acid, 2,2-dihydroxymethylbutyric acid, naphthalene phenol, 3,5-dihydroxybenzoic acid or 3,4,5-trihydroxybenzoic acid; the catalyst is potassium isooctanoate, dioctyltin dithiol, dibutyltin oxide, dibutyltin diacetate or phenylmercuric propionate; the neutralizer is triethylamine, ammonia water or sodium hydroxide.
20. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the polymeric polyol is polytetramethylene glycol.
21. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the polyisocyanate is dimethyl diphenyl diisocyanate.
22. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the organic solvent is N-methylpyrrolidone.
23. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the chain extender is 2,2-dihydroxymethylbutyric acid.
24. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the catalyst is dibutyltin diacetate.
25. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (2), the neutralizing agent is triethylamine.
26. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), 45 ml of water-based ceramic / polyurethane hybrid prepolymer is measured.
27. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), the ratio of the amount of the foaming agent and the stabilizer added to the material of the water-based ceramic / polyurethane hybrid prepolymer is 8g:0.3mg:45ml.
28. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), the foaming agent is azodicarbonamide.
29. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), the stabilizer is citric acid, sodium alginate or sodium dodecylbenzene sulfonate.
30. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), the stabilizer is sodium dodecylbenzene sulfonate.
31. The method for preparing moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 1, characterized in that: In step (3), the surface drying and curing parameters during coating are as follows: the temperature of the 6-section oven is controlled at 50~60℃-80~100℃-110~120℃-110~140℃-105~160℃-60~90℃, the speed of the unwinding machine is 40~90m / min, the unwinding tension is 25~50N / m, and the winding tension is 32~55N / m.
32. The method for preparing the moisture-locking and aroma-retaining ceramic-coated specialty paper according to claim 31, characterized in that: In step (3), the surface drying and curing parameters during coating are: the temperature of the 6-section oven is controlled at 52°C-83°C-115°C-120°C-135°C-70°C, the unwinding and winding machine speed is 70m / min, the unwinding tension is 31N / m, and the winding tension is 47N / m.
33. Moisture-locking and aroma-retaining ceramic-coated specialty paper prepared according to any one of claims 1 to 32.
Citation Information
Patent Citations
Method for preparing polyurethane hybridization material for hydroxyl-containing filler
CN102558828A
Cigarette aroma and moisture keeping pottery clay packing paper, method for preparing same and packing box
CN108374294A
Environment-friendly and degradable micro-sponge type moistening, fresh-keeping and aroma-enhancing packaging paper and preparation method
CN109235124A
Application of multi-layer graphite microchip composite polymer material used in anticorrosive coating
CN110028823A